USM OFFERS EXPERTISE 21 IN NEUROSCIENCE - MPRC, Pusat Media & Perhubungan Awam (2017)
KUBANG KERIAN, KELANTAN,21 February 2017 The human brain plays a very important role in human anatomy, in optimising the quality of life by ensuring that normal functions of intelligence, senses, motor movements and behaviours are wellcoordinated.